Interactions Between Air Pollution and Pollen Season for Rhinitis Using Mobile Technology: A MASK-POLLAR Study - Bédard, Annabelle; Sofiev, Mikhail; Arnavielhe, Sylvie; Antó, Josep M; Garcia-Aymerich, Judith; Thibaudon, Michel; Bergmann, Karl Christian; Dubakiene, Ruta; Bedbrook, Anna; Onorato, Gabrielle L; Annesi-Maesano, Isabella; Pépin, Jean-Louis; et al. (The journal of allergy and clinical immunology in practice (Cambridge, MA), 2020)
Several studies have suggested an interaction between air pollution and pollen exposure with an impact on allergy symptoms. However, large studies with real-life data are not available. To investigate associations between major air pollutants (ozone and particulate matter with a diameter of <2.5 μm) and allergic rhinitis (AR) control during grass and birch pollen seasons as well as outside the pollen season. The daily impact of allergic symptoms was recorded by the Allergy Diary (Mobile Airways Sentinel NetworK [MASK-air]) app (a validated mHealth tool for rhinitis management) using visual analog scales (VASs) in Northern and Central Europe users in 2017 and 2018. Uncontrolled AR was defined using symptoms and medications. Pollutant levels were assessed using the System for Integrated modeLing of Atmospheric coMposition database. Pollen seasons were assessed by regions using Google Trends. Generalized estimating equation models were used to account for repeated measures per user, adjusting for sex, age, treatment, and country. Analyses were stratified by pollen seasons to investigate interactions between air pollutants and pollen exposure. A total of 3323 geolocated individuals (36,440 VAS-days) were studied. Associations between uncontrolled rhinitis and pollutants were stronger during the grass pollen season. Days with uncontrolled AR increased by 25% for an interquartile range increase in ozone levels during the grass pollen season (odds ratio of 1.25 [95% CI, 1.11-1.41] in 2017 and of 1.14 [95% CI, 1.04-1.25] in 2018). A similar trend was found for particulate matter with a diameter of less than 2.5 μm, especially in 2017. These results suggest that the relationship between uncontrolled AR and air pollution is modified by the presence of grass pollens. This study confirms the impact of pollutants in the grass pollen season but not in the birch pollen season.